The Performance of Tapered Feed Network and Quarter-Wavelength Transformer Feed Network at KU-Band - Lai, Tian Fat; Mahadi, Wan Nor Liza; Soin, Norhayati (IEEE, 2009)
This paper presents the performance of 4×4 array tapered microstrip feed network and quarter-wavelength transformer feed network at KU-Band. The paper shows the comparison of S11 and VSWR parameters between two feed networks at 15GHz. ADS2008 simulation software was used to present the useful results on both the networks at 15GHz.